PERSEPSI PENYANDANG DISABILITAS TERHADAP PELUANG KARIER DI DUNIA KERJA FORMAL: STUDI KASUS PADA UNIPARMART, PT SUMBER ALFARIA TRIJAYA TBK CABANG JEMBER - Moch. Anas Kurniawan (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to explore the perceptions of persons with disabilities regarding career opportunities in the formal work environment at UNIPARMART, PT Sumber Alfaria Trijaya Tbk, Jember Branch. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving employees with disabilities and company management. The findings indicate that while the recruitment process has become more accessible, physical accessibility and career development remain limited. The social environment is supportive, but it is not yet accompanied by a fully inclusive managerial system. This research recommends improving physical accessibility, establishing training policies, and strengthening inclusive work systems to support sustainable careers for persons with disabilities.